An additional ✝Archearadinae flat-bug species from Cretaceous Burmese Amber (Hemiptera, Aradidae) - Royce T. Cumming; Julia J. Mlynarek (ZooKeys)
Currently 19 species of Aradidae (flat bugs) are known from the Cretaceous deposits of Burma (Burmese/Kachin amber). In reviewing unidentified aradid species from this deposit, an unnamed species was located. This aradid includes a unique combination of features from several Cretaceous aradid genera coupled with apomorphic antennae morphology allows easy differentiation from other aradids. Therefore, a new genus and species is herein described as Sauronaradus meganae gen. et. sp. nov. to accommodate these unique features.